Kualitas Sistem, Kecanggihan Teknologi, Kemampuan Teknik Personal dan Efektivitas Sistem Informasi Akuntansi - Ari, Ni Made Tini; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p02, 2023)
The research aims to determine the effect of information system quality, information technology sophistication and personal technical skills on the effectiveness of the Village Credit Institution accounting information system. The sample of this study was 18 LPD with the method of determining the sample using a purposive sampling technique. Research data collection was carried out by distributing questionnaires. The data analysis technique used in this research is multiple linear regression. The results showed that the quality of information systems, information technology sophistication and personal technical skills had a positive effect on the effectiveness of accounting information systems. The research results are expected to contribute to the TAM concept in explaining the relationship between the influence of information system quality, information technology sophistication, and personal technical skills on the effectiveness of AIS. Keywords: Information System Quality, Information Technology Sophistication, Personal Technical Ability, Accounting Information System Effectiveness.